PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH KOPERASI SIMPAN PINJAM DANA ARTA MANDIRI KABUPATEN PURWAKARTA - Tiara Yustika; Rita Mardiana (Institut Bisnis Muhammadiyah Bekasi, 2023)
The purpose of this study is to focus on analysis to determine whether there is an influence of service quality on customer satisfaction at KSP (Koperasi Simpan Pinjam) Dana Arta Mandiri, Purwarkarta. The distribution of questionnaires to 100 KSP Dana Arta Mandiri customers with sampling techniques using purposive sampling. The research method used is a descriptive quantitative method. Data analysis techniques use descriptive analysis testing, research instrument testing, classical assumption testing, hypothesis testing of simple linear regression analysis, and coefficient of determination testing with the help of the SPSS application program version 25. The results of this study are known that the quality of service has a significant effect on customer satisfaction at KSP Dana Arta Mandiri of 4,645 > 1,984 and 0.000 < 0.05.R2